Food, drink, and the trickster: a literary exploration of cultural themes and values in the Maqamat al-hamadhani - Hussam Abdullah Almujalli (Cogent Arts & Humanities)
In this article, I examine the literal and metaphoric cultural themes and values in the Maqamat al-Hamadhani, a significant literary work in Arabic culture in the eleventh century a.d. I specifically focus on the ways in which the trickster protagonist in the stories uses food and drink to trick people to obtain what he wants. First, I provide a brief overview of the maqama genre of Arabic literature, following that with an analysis of cultural themes and spiritual values in the selected stories. I have identified the trickster archetype as a central character in the stories, who uses his wit and humor to navigate the Islamic social world. I examine how the trickster is depicted in the Maqamat al-Hamadhani, and how this characterization is linked to food and drink. I also examine how food and drink are used as a tool to promote self-preservation, compassion, advice, self-awareness, language and wisdom, learning from experience, life’s pleasures and giving blessings, sincerity, humor, laughter, and feeding the soul. I conclude that the trickster is a model for how food and language feed the soul. Notably, food satisfies and nourishes both the body and the spirit by satisfying physical appetite and bringing energy to the spirit. Language serves the same purpose, particularly if it is eloquent.